Penetapan Sanksi Hukum untuk Anggota Majelis Pengawas Notaris yang Tidak Melaksanakan Tanggung Jawab Pengawasan - Konradus Lalo; Herlindah Herlindah; Dyah Aju Wisnuwardhani (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
This research aims to find out and analyze the determination of sanctions for members of the notary supervisory board who do not carry out their supervisory responsibilities both on a legal basis and on the procedures for determining them. This research uses normative legal research methods with a statutory approach. The results of this research explain that sanctions related to notary violations are regulated by Article 15, Article 16, Article 17, Article 19 UUJN, and Article 4 of the Notary's Code of Ethics. However, there are no provisions that regulate specific sanctions for the Notary Supervisory Board who do not carry out their supervisory responsibilities properly. This creates challenges in enforcing discipline and accountability among its members. The lack of clarity in these regulations can provide an opening for potential violations of ethics or authority without guaranteeing that appropriate corrective action will be taken to maintain the integrity and standards of the notary profession. Therefore, revising regulations or establishing more detailed guidelines regarding sanctions for members of the Notary Supervisory Board is an urgent step to ensure effectiveness and fairness in carrying out its supervisory function.